2017
DOI: 10.12669/pjms.332.11847
|View full text |Cite
|
Sign up to set email alerts
|

Borderline tumors of the ovary: A clinicopathological study

Abstract: Objective:To report experience with borderline ovarian tumors (BOTs) in a developing country like Pakistan with limited resources and weak database of health system.Methods:Patients with BOTs managed at Shaukat Khanum Cancer hospital, Lahore, Pakistan from 2004 to 2014 were included and reviewed retrospectively. Data was recorded on histopathological types, age, CA-125, stage of disease, treatment modalities and outcomes.Results:Eighty-six patients with BOT were included with a median age of 35 years. Forty-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Recurrence rates vary in different studies ( 1 ). A systematic review ( 6 ) showed that 37% of recurrences are diagnosed during the first 2 years, 31% in years 2–5, and 32% more than 5 years after diagnosis, including 10% after more than 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrence rates vary in different studies ( 1 ). A systematic review ( 6 ) showed that 37% of recurrences are diagnosed during the first 2 years, 31% in years 2–5, and 32% more than 5 years after diagnosis, including 10% after more than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, evaluation of the nodule size, which might be related to BOTs according to the RECIST (Response Evaluation Criteria in Solid Tumors) guideline ( 9 ), may be helpful to monitor malignant transformation or malignancy recurrence. In one retrospective review, age ≥40 years, a late stage at diagnosis and incomplete surgery were significantly associated with invasive recurrence, while complete tumor excision and a prolonged follow-up were advised for cases in which malignant transformation may occur ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently more studies have attempted to quantify the success of fertility after conservative surgery. 12 This should be considered and discussed with the patient prior to treatment and may include fertility counseling.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MBOTs, approximately 32% of BOTs [ 8 ], occur predominately in East Asia and parts of Europe [ 9 ]. BOTs are predominantly diagnosed in premenopausal females before the age of 40 and are rarely confirmed in older women after the age of 65 [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%